Synthesis of N-alkyl-C α, α-dimethylglycine derivatives - Monteiro, Luís S. (2014)
The application of trialkyloxonium tetrafluoroborates for N-alkylation of the nonnatural amino acid Cα, α-dimethylglycine is described. Several methyl esters of dimethylglycine protected with different amine protecting groups were subject to N-ethylation or N-methylation with triethyloxonium tetrafluoroborate or trimethyloxonium tetrafluoroborate, respectively. The corresponding N-akyl-Cα, α-dimethylglycine derivatives were obtained in good to high yields. Removal of the methyl ester rendered amino acid derivatives ready for application in peptide synthesis.